МІСЦЕ УКРАЇНЦІВ У РАМКАХ РОСІЙСЬКОЇ ІМПЕРІЇ (Zaporizhzhia Historical Review, 2021)
Nowadays, when the relations between Ukraine and Russia leave much to be desired, we would like to recall the times when the czarist regime formed its attitude towards the Ukrainians as to the followers of Mazepa, the Khokhly, the Malaia Russians. The Ukrainian people remained under the opression of the czarism for more than 250 years. Its policy changed, but the superiority of the Russians towards the Ukrainians was stable. Thus, it is not surprising that at present time the Russian politicians still can not understand the reason why the Ukrainians are making some attempts to ratify the language, the culture and the state of their own.